2016
DOI: 10.1080/09500693.2016.1191089
|View full text |Cite
|
Sign up to set email alerts
|

Learning nanotechnology with texts and comics: the impacts on students of different achievement levels

Abstract: Comics are popular with adolescents because of their features of humor, narrative, and visual imagery. The purposes of this study were to examine the learning outcomes and emotional perceptions of reading a science comic book and a science text booklet for students of different levels of achievement, and to explore the main factors of the two media which attract highschool students to learn science. A mixed-method quasiexperimental design was adopted. The participants were 697 grade ten students from eight sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 25 publications
0
41
0
2
Order By: Relevance
“…They can be used as a vehicle through which (scientific) information is communicated (Arroio, 2011;Kennepohl & Roesky, 2008;Tatalovic, 2009). As a creative approach to science, they can represent real-world situations which have no clear answer, be interdisciplinary in nature, prove relevant to both the curriculum and students´ lives, and remain highly visible and accessible (Arroio, 2011;Hosler & Boomer, 2011;Lin & Lin, 2016). This can improve students' skills in dealing with everyday life and with socio-scientific issues.…”
Section: General Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…They can be used as a vehicle through which (scientific) information is communicated (Arroio, 2011;Kennepohl & Roesky, 2008;Tatalovic, 2009). As a creative approach to science, they can represent real-world situations which have no clear answer, be interdisciplinary in nature, prove relevant to both the curriculum and students´ lives, and remain highly visible and accessible (Arroio, 2011;Hosler & Boomer, 2011;Lin & Lin, 2016). This can improve students' skills in dealing with everyday life and with socio-scientific issues.…”
Section: General Frameworkmentioning
confidence: 99%
“…A review of the literature shows that some research on the use of comics in science lessons has already been carried out (Hosler & Boomer, 2011;Lin & Lin, 2016;Spiegel et al, 2013;Tatalovic, 2009). A study by Kerneza and Kosir (2016) indicated a positive effect on reading literacy and reading motivation.…”
Section: General Frameworkmentioning
confidence: 99%
See 3 more Smart Citations